Hair repairing composition containing 3D structure cationic polymer and preparation method of hair repairing composition
By using hair care compositions containing 3D structure cationic polymers in hair care products, the problem of disulfide bond repair after hair damage is solved, the hair is light and fluffy and good combing of dry and wet hair is achieved, and the user experience is improved.
Patent Information
- Application Number
- CN202510075983.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-22
AI Technical Summary
Existing hair care products are difficult to effectively repair the disulfide bond after hair is damaged, which can easily destroy the internal structure, resulting in thick and sticky hair, and the hair is hard and fragile after long-term use.
Using a hair repair composition containing a 3D structure cationic polymer, the hair is light and fluffy by neutralizing the negative charge on the hair, and the conditioner is spread smoothly and evenly on the hair through a unique spherical structure.
It realizes repairing damaged hair from the internal structure, making the hair light and fluffy, and improving the combing properties of dry and wet hair. After applying, rinsing or drying, the hair is smooth and refreshing, not sticky, and has a good experience.
Smart Images

Figure CN119857065A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hair repair, and in particular to a hair repair composition containing a 3D structured cationic polymer and a preparation method thereof. Background Art
[0002] CN118766779A A pandamide-based hair care composition for repairing disulfide bonds of damaged hair and a preparation method thereof. Although the present invention effectively solves the problem of difficulty in repairing disulfide bonds of damaged hair and easy destruction of the internal structure in existing hair care products, and achieves the repair of damaged hair from the internal structure, the product experience is not good, the material is thick, the flushing process is very sticky, and the hair feels obviously heavy after drying.
[0003] CN115093569A discloses an amino silicone oil and a preparation method thereof and use thereof in the preparation of a protein repair hair conditioner. Although the amino silicone oil can repair hair damage and form a complete amino silicone oil protective layer, enhance hair toughness and provide long-term protection for hair, the amino silicone oil contains a large amount of amino groups at its nodes, resulting in too strong a bonding force with the hair. After long-term use, the hair becomes too hard and brittle and has insufficient toughness.
[0004] Traditional amino silicone oil has the defects of poor hydrophobicity and gloss, and is easy to turn yellow. Amino silicone oil with high nitrogen content makes hair sticky, hardens and deteriorates after use. At the same time, the addition of protein alone cannot perfectly combine with the protein in the hair scale layer and cortex layer. Under the influence of external factors (light, water immersion, pH), it is easy to lose its repair effect. Summary of the invention
[0005] In order to repair damaged hair, especially to solve the problem of stickiness caused by amino-terminated polydimethylsiloxane after drying hair, the present invention provides a hair repair composition containing a 3D structured cationic polymer. The addition of the 3D structured cationic polymer can neutralize the negative charge on the hair, making the hair light and fluffy; its unique spherical structure allows keratin, amino-terminated polydimethylsiloxane, polydimethylsiloxane and other hair conditioners to be spread smoothly and evenly on the hair, bringing a smooth and pleasant fluffy texture; at the same time, it improves the combing properties of dry and wet hair, especially making the hair just after application, rinsing or drying very smooth, refreshing, non-sticky and having a good experience.
[0006] The present invention provides a hair repair composition containing a 3D structured cationic polymer, characterized in that it comprises the following components in weight fractions:
[0007] Hair conditioning agent 5-14%, thickener 0.1-0.5%, emulsion stabilizer 7-9%, antistatic agent 1.4-3.0%, pH adjuster 0.15%, preservative 0.2-0.4%, chelating agent 0.1% and deionized water 75-85%;
[0008] The hair conditioning agent includes a 3D structured cationic polymer, keratin, amino dimethicone and polydimethicone.
[0009] As an improvement of the hair repair composition containing 3D structure cationic polymer of the present invention, the hair conditioner comprises 0.5-2.5% of 3D structure cationic polymer, 0.02-1% of keratin, 3-8% of amino terminal polydimethylsiloxane and 0.5-4% of polydimethylsiloxane.
[0010] As an improvement of the hair repair composition containing a 3D structured cationic polymer of the present invention, the keratin further comprises hydrolyzed keratin or oxidized keratin, and the 3D structured cationic polymer is polyquaternium-52.
[0011] As an improvement of the hair repair composition containing 3D structured cationic polymer of the present invention, the thickener is 0.1-0.5% of hydroxyethyl cellulose.
[0012] As an improvement of the hair repair composition containing 3D structure cationic polymer of the present invention, the emulsifying stabilizer is 7-9% of fatty alcohol (C16 / 18).
[0013] As an improvement of the hair repair composition containing 3D structure cationic polymer of the present invention, the antistatic agent is 1.2-2.0% of stearyl trimethyl ammonium chloride and 0.2-1.0% of behenyl trimethyl ammonium chloride.
[0014] As an improvement of the hair repair composition containing a 3D structured cationic polymer of the present invention, the pH value regulator is 0.15% lactic acid.
[0015] As an improvement of the hair repairing composition containing 3D structured cationic polymer of the present invention, the preservatives are 0.3% DMDM hydantoin and 0.05% kason.
[0016] As an improvement of the hair repair composition containing a 3D structured cationic polymer of the present invention, the chelating agent is 0.1% disodium EDTA.
[0017] The present invention provides a method for preparing a hair repair composition containing a 3D structured cationic polymer, wherein the composition is prepared by the following steps:
[0018] S1. First pour deionized water into the emulsifying pot, then add the chelating agent, stir at room temperature, then sprinkle the hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0019] S2. After the emulsifying pot is heated to 80-85°C, add stearyl trimethyl ammonium chloride and behenyl trimethyl ammonium chloride in sequence, and stir at 80-85°C until dissolved evenly;
[0020] S3. Place fatty alcohol (C16 / 18) in the oil phase pot and heat to 80-85°C until completely dissolved, then pour into the emulsifier pot, stir evenly and homogenize for 3-5 minutes, continue to keep at 80-85°C and stir at medium speed for 15-20 minutes before starting to cool down;
[0021] S4. After the temperature drops to 55-60°C, add aminodimethylsiloxane and polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0022] S5. After the temperature drops to 40-45°C, add polyquaternium-52, keratin, lactic acid and preservatives in sequence. Stir for about 20 minutes to mix well.
[0023] As an improvement of the preparation method of a hair repair composition containing a 3D structured cationic polymer of the present invention, the weight fractions of the components are as follows:
[0024] The deionized water is 75-85%, the chelating agent is 0.1%, the hydroxyethyl cellulose is 0.1-0.5%, the stearyl trimethyl ammonium chloride is 1.2-2.0%, the behenyl trimethyl ammonium chloride is 0.2-1.0%, the fatty alcohol (C16 / 18) is 7-9%, the amino-terminated polydimethylsiloxane is 3-8%, the polydimethylsiloxane is 0.5-4%, the polyquaternium-52 is 0.5-2.5%, the keratin is 0.02-1%, the preservative is 0.2-0.4%, and the pH regulator is 0.15%.
[0025] The present invention discloses a hair repair composition containing a 3D structured cationic polymer and a preparation method thereof, and has the following beneficial effects: the 3D structured cationic polymer is a cationic spherical polymer, which can neutralize the negative charge on the hair and make the hair light and fluffy; its unique spherical structure enables keratin, amino-terminated polydimethylsiloxane, polydimethylsiloxane and other hair conditioners to be smoothly and evenly spread on the hair, bringing a smooth and pleasant fluffy texture; at the same time, it improves the combing properties of wet and dry hair, especially making the hair just after application, rinsing or drying very smooth, refreshing, non-sticky and having a good experience. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a photograph of a 3D structured cationic polymer in a hair repair composition containing the 3D structured cationic polymer according to the present invention.
[0027] Figure 2 This is a moderate irritation picture of the test substance of Comparative Example 4 of a hair repairing composition containing a 3D structured cationic polymer of the present invention.
[0028] Figure 3This is a picture showing the non-irritating / mildly irritating properties of the test substance of Example 1 of a hair repairing composition containing a 3D structured cationic polymer of the present invention.
[0029] Figure 4 These are photos of the hair repairing composition in Example 1 of the present invention containing a 3D structured cationic polymer (normal photo on the right) and the hair repairing composition in Comparative Example 4 (reddened photo on the left).
[0030] Figure 5 These are photos of the hair bundle after drying in Example 1 of a hair repair composition containing a 3D structured cationic polymer of the present invention (photo on the right, good fluffiness) and the hair bundle after drying in Comparative Example 7 (photo on the left, not fluffy and with a strong sticky feeling).
[0031] Figure 6 It is a schematic diagram of the preparation process of Example 1 of a method for preparing a hair repair composition containing a 3D structured cationic polymer of the present invention. DETAILED DESCRIPTION
[0032] Below, combined with the attached Figure 1-6 As well as a specific implementation method, a hair repair composition containing a 3D structured cationic polymer and a preparation method thereof of the present invention are further described. It should be noted that, under the premise of no conflict, the various technical features described below can be arbitrarily combined to form a new embodiment.
[0033] refer to Figure 1 In a preferred embodiment, the 3D structured cationic polymer is polyquaternium-52, which is a cationic spherical polymer that can neutralize the negative charge on the hair, making the hair light and fluffy; its unique spherical structure allows keratin, amino-terminated polydimethylsiloxane, polydimethylsiloxane and other hair conditioning agents to be spread smoothly and evenly on the hair, bringing a smooth and pleasant texture; at the same time, it improves the combing of dry and wet hair, especially making the hair just after application, rinsing or drying very smooth, refreshing, non-sticky, and good experience;
[0034] The molecular formula of the polyquaternium salt-52 is as follows:
[0035]
[0036] In a preferred embodiment, the keratin is hydrolyzed keratin and oxidized keratin extracted from wool, including macromolecular proteins and small molecular functional polypeptides. The macromolecular proteins maintain the biological activity of keratin and have a film-forming effect. The small molecular functional polypeptides are easily absorbed through the biological membrane and protect and maintain the activity of cystine. They all belong to functional keratin. Functional keratin has good effects of protecting hair, repairing damaged hair, promoting skin repair, accelerating wound healing, etc. On hair, functional keratin contains a high proportion of cystine, which can form disulfide bonds with human hair fibers to repair hair. In addition, it can also strengthen hair and reduce breakage. Functional keratin protects the unique amino acid sequence structure, has 91% similarity with human keratin, contains a high content of cystine, and has the effect of scavenging free radicals. The small molecular polypeptide can penetrate into the cortex and skin of damaged hair fibers to strengthen hair.
[0037] Embodiment 1:
[0038] refer to Figure 6 Example 1 provides a hair care composition containing a 3D structured cationic polymer, comprising 8% fatty alcohol, 0.3% hydroxyethyl cellulose, 5% amino dimethicone, 4% polydimethicone, 1.5% polyquaternium-52, 0.3% keratin, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin, 0.05% kasone and deionized water, wherein the composition is prepared by the following steps:
[0039] 101. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.3% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0040] 102. After the emulsifying pot is heated to 83°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and stir at 83°C until they are evenly dissolved;
[0041] 103. Place 8% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifying pot, stir evenly and homogenize for 4 minutes, continue to keep at 83°C and stir at medium speed for 18 minutes before starting to cool down;
[0042] 104. After the temperature drops to 58°C, add 5% amino-terminated polydimethylsiloxane and 4% polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0043] 105. After the temperature drops to 43°C, add 1.5% polyquaternium-52, 0.3% keratin, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix well.
[0044] In Example 1, the polyquaternium salt-52, as a cationic spherical polymer, neutralizes the negative charge of the hair, making the hair light and fluffy; its unique spherical structure allows keratin, amino dimethicone, polydimethicone and other hair conditioning agents to be spread smoothly and evenly on the hair, bringing a smooth and pleasant fluffy texture; at the same time, it improves the combing of dry and wet hair, especially making the hair just after application, rinsing or drying very smooth, refreshing, non-sticky, and good experience
[0045] Embodiment 2:
[0046] Example 2 provides a hair repair composition containing a 3D structured cationic polymer, comprising 9% fatty alcohol, 0.5% hydroxyethyl cellulose, 8% amino dimethicone, 0.5% polydimethicone, 2.5% polyquaternium-52, 0.02% keratin, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin, 0.05% kason and deionized water, and the composition is prepared by the following steps:
[0047] S1. Pour deionized water into an emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.5% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on heating;
[0048] S2. After the emulsifying pot is heated to 83°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and stir at 83°C until the mixture is evenly dissolved.
[0049] S3. Place 9% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifier pot, stir evenly and homogenize for 3 minutes, continue to keep at 83°C and stir at medium speed for 15 minutes before starting to cool down;
[0050] S4, after the temperature drops to 58°C, add 8% amino-terminated polydimethylsiloxane and 0.5% polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0051] S5. After the temperature drops to 43°C, add 2.5% polyquaternium-52, 0.02% keratin, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix well.
[0052] In Example 2, the hair repair composition has high viscosity and is in a paste form. The polyquaternium-52, as a cationic spherical polymer, neutralizes the negative charge of the hair and makes the hair light and fluffy.
[0053] Embodiment 3:
[0054] Example 3 provides a hair repair composition containing a 3D structured cationic polymer, which includes 7% fatty alcohol, 0.1% hydroxyethyl cellulose, 3% amino dimethicone, 4% polydimethicone, 0.2% polyquaternium-52, 1% keratin, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin, 0.05% kason and deionized water. The composition is prepared by the following steps:
[0055] S1. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.1% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0056] S2. After the emulsifying pot is heated to 83°C, add stearyl trimethyl ammonium chloride and behenyl trimethyl ammonium chloride in sequence, and stir at 83°C until the mixture is evenly dissolved.
[0057] S3. Place 7% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifier pot, stir evenly and homogenize for 5 minutes, continue to keep at 83°C and stir at medium speed for 20 minutes before starting to cool down;
[0058] S4, after the temperature drops to 58°C, add 3% amino-terminated polydimethylsiloxane and 4% polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0059] S5. After the temperature drops to 43°C, add 0.2% polyquaternium-52, 1% keratin, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix well.
[0060] In Example 3, the hair repair composition has low viscosity and is flowable. Polyquaternium-52 is a cationic spherical polymer. Its unique spherical structure allows keratin, amino dimethicone, polydimethicone and other hair conditioning agents to be spread smoothly and evenly on the hair, bringing a smooth and pleasant fluffy texture.
[0061] Comparative Example 1:
[0062] Comparative Example 1 provides a hair repair composition, which includes 8% fatty alcohol, 0.3% hydroxyethyl cellulose, 5% amino dimethicone, 4% polydimethicone, 0.3% keratin, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin, 0.05% kason and deionized water. The composition is prepared by the following steps:
[0063] S1. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.3% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0064] S2. After the emulsifying pot is heated to 83°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and stir at 83°C until the mixture is evenly dissolved.
[0065] S3. Place 8% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifying pot, stir evenly and homogenize for 4 minutes, continue to keep at 83°C and stir at medium speed for 18 minutes before starting to cool down;
[0066] S4, after the temperature drops to 58°C, add 5% amino-terminated polydimethylsiloxane and 4% polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0067] S5. After the temperature drops to 43°C, add 0.3% keratin, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix evenly.
[0068] Compared with Example 1, the hair composition of Comparative Example 1 does not contain the 3D structured cationic polymer component, namely, polyquaternium-52, so the hair does not feel light and fluffy after use.
[0069] Comparative Example 2:
[0070] Comparative Example 2 provides a hair repair composition containing a 3D structured cationic polymer, which includes 8% fatty alcohol, 0.3% hydroxyethyl cellulose, 5% amino dimethicone, 4% polydimethicone, 1.5% polyquaternium-52, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin, 0.05% kason and deionized water, and the composition is prepared by the following steps:
[0071] S1. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.3% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0072] S2. After the emulsifying pot is heated to 83°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and stir at 83°C until the mixture is evenly dissolved.
[0073] S3. Place 8% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifying pot, stir evenly and homogenize for 4 minutes, continue to keep at 83°C and stir at medium speed for 18 minutes before starting to cool down;
[0074] S4, after the temperature drops to 58°C, add 5% amino-terminated polydimethylsiloxane and 4% polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0075] S5. After the temperature drops to 43°C, add 1.5% polyquaternium-52, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix evenly.
[0076] Compared with Example 1, the hair composition of Comparative Example 2 has a general effect of smoothing frizzy hair and general combing properties for both wet and dry hair because no keratin component is added.
[0077] Comparative Example 3:
[0078] Comparative Example 3 provides a hair repair composition containing a 3D structured cationic polymer, which includes 8% fatty alcohol, 0.3% hydroxyethyl cellulose, 4% polydimethylsiloxane, 1.5% polyquaternium-52, 0.3% keratin, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin, 0.05% kason and deionized water. The composition is prepared by the following steps:
[0079] S1. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.3% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0080] S2. After the emulsifying pot is heated to 83°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and stir at 83°C until the mixture is evenly dissolved.
[0081] S3. Place 8% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifying pot, stir evenly and homogenize for 4 minutes, continue to keep at 83°C and stir at medium speed for 18 minutes before starting to cool down;
[0082] S4, after the temperature drops to 58°C, add 4% polydimethylsiloxane in sequence and stir quickly to mix evenly;
[0083] S5. After the temperature drops to 43°C, add 1.5% polyquaternium-52, 0.3% keratin, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix evenly.
[0084] Compared with Example 1, in Comparative Example 3, since the hair composition does not contain amino dimethicone, the smoothness during the rinsing stage is not sustained, and the combing properties of wet hair are average.
[0085] Comparative Example 4:
[0086] Comparative Example 4 provides a hair repair composition containing a 3D structured cationic polymer, which includes 8% fatty alcohol, 0.3% hydroxyethyl cellulose, 5% amino dimethicone, 4% polydimethicone, 3% polyquaternium-52, 1.2% keratin, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin, 0.05% kason and deionized water, and the composition is prepared by the following steps:
[0087] S1. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.3% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0088] S2. After the emulsifying pot is heated to 83°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and stir at 83°C until the mixture is evenly dissolved.
[0089] S3. Place 8% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifying pot, stir evenly and homogenize for 4 minutes, continue to keep at 83°C and stir at medium speed for 18 minutes before starting to cool down;
[0090] S4, after the temperature drops to 58°C, add 5% amino-terminated polydimethylsiloxane and 4% polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0091] S5. After the temperature drops to 43°C, add 3% polyquaternium-52, 1.2% keratin, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix evenly.
[0092] Compared with Example 1, the hair composition of Comparative Example 4 has too much polyquaternium salt-52 and too much keratin, so the heat resistance test of the composition is unstable and discoloration occurs; and the mildness test is moderately irritating.
[0093] Comparative Example 5:
[0094] Comparative Example 5 provides a hair repair composition, which includes 8% fatty alcohol, 0.3% hydroxyethyl cellulose, 4% polydimethylsiloxane, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin and 0.05% kason and deionized water. The composition is prepared by the following steps:
[0095] S1. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.3% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0096] S2. After the emulsifying pot is heated to 85°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and keep the temperature at 83°C and stir until the mixture is evenly dissolved;
[0097] S3. Place 8% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifier pot, stir evenly and homogenize for 5 minutes, continue to keep at 83°C and stir at medium speed for 20 minutes before starting to cool down;
[0098] S4, after the temperature drops to 58°C, add 4% polydimethylsiloxane in sequence and stir quickly to mix evenly;
[0099] S5. After the temperature drops to 43°C, add 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix evenly.
[0100] In Comparative Example 5, no 3D structured cationic polymer, keratin, or amino dimethicone was added, resulting in the worst hair volume and the worst wet and dry hair combing properties.
[0101] Comparative Example 6:
[0102] Comparative Example 6 provides a hair repair composition, which includes 8% fatty alcohol, 0.3% hydroxyethyl cellulose, 0.5% amino dimethicone, 4% polydimethicone, 0.3% keratin, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin and 0.05% kason and deionized water. The composition is prepared by the following steps:
[0103] S1. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.3% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0104] S2. After the emulsifying pot is heated to 85°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and keep the temperature at 83°C and stir until the mixture is evenly dissolved;
[0105] S3. Place 8% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifier pot, stir evenly and homogenize for 5 minutes, continue to keep at 83°C and stir at medium speed for 20 minutes before starting to cool down;
[0106] S4, after the temperature drops to 58°C, add 0.5% amino-terminated polydimethylsiloxane and 4% polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0107] S5. After the temperature drops to 43°C, add 0.3% keratin, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix evenly.
[0108] In Comparative Example 6, very little amino dimethicone was added, and no 3D structured cationic polymer was added for effective and uniform spreading, resulting in insufficient conditioning.
[0109] Comparative Example 7:
[0110] Comparative Example 7 provides a hair repair composition, which includes 8% fatty alcohol, 0.3% hydroxyethyl cellulose, 10% amino dimethicone, 4% polydimethicone, 0.3% keratin, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin and 0.05% kason and deionized water. The composition is prepared by the following steps:
[0111] S1. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.3% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0112] S2. After the emulsifying pot is heated to 85°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and keep the temperature at 83°C and stir until the mixture is evenly dissolved;
[0113] S3. Place 8% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifier pot, stir evenly and homogenize for 5 minutes, continue to keep at 83°C and stir at medium speed for 20 minutes before starting to cool down;
[0114] S4, after the temperature drops to 58°C, add 10% amino-terminated polydimethylsiloxane and 4% polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0115] S5. After the temperature drops to 43°C, add 0.3% keratin, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix evenly.
[0116] In Comparative Example 7, a lot of amino-terminated polydimethylsiloxane was added, but the effect of adding a 3D structured cationic polymer was not achieved. Since amino-terminated polydimethylsiloxane has a strong sedimentation property, the material becomes sticky, the hair is not fluffy, and the shampooing experience is not good.
[0117] Comparative Example 8:
[0118] Comparative Example 8 provides a hair repair composition, which includes 8% fatty alcohol, 0.3% hydroxyethyl cellulose, 0.5% amino dimethicone, 4% polydimethicone, 23% polyquaternium-5, 0.01% keratin, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin and 0.05% kason and deionized water. The composition is prepared by the following steps:
[0119] S1. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.3% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0120] S2. After the emulsifying pot is heated to 85°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and keep the temperature at 83°C and stir until the mixture is evenly dissolved;
[0121] S3. Place 8% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifier pot, stir evenly and homogenize for 5 minutes, continue to keep at 83°C and stir at medium speed for 20 minutes before starting to cool down;
[0122] S4, after the temperature drops to 58°C, add 0.5% amino-terminated polydimethylsiloxane and 4% polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0123] S5. After the temperature drops to 43°C, add 0.01% keratin, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix well.
[0124] In Comparative Example 8, very little keratin was added and no 3D structured cationic polymer was added for effective and uniform spreading, resulting in insufficient conditioning.
[0125] Comparative Example 9:
[0126] Comparative Example 9 provides a hair repair composition with polyquaternium-52 as a raw material, which includes 8% fatty alcohol, 0.3% hydroxyethyl cellulose, 0.5% amino dimethicone, 4% polydimethicone, 1.5% keratin, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin and 0.05% kason and deionized water. The composition is prepared by the following steps:
[0127] S1. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.3% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0128] S2. After the emulsifying pot is heated to 85°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and keep the temperature at 83°C and stir until the mixture is evenly dissolved;
[0129] S3. Place 8% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifier pot, stir evenly and homogenize for 5 minutes, continue to keep at 83°C and stir at medium speed for 20 minutes before starting to cool down;
[0130] S4, after the temperature drops to 58°C, add 0.5% amino-terminated polydimethylsiloxane and 4% polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0131] S5. After the temperature drops to 43°C, add 1.5% keratin, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix well.
[0132] In Comparative Example 9, a lot of keratin was added, but no 3D structured cationic polymer was added for effective and uniform spreading, resulting in a strong irritation to the formula. The excessive keratin component also caused the stability test to fail, mainly due to heat-resistant unstable discoloration.
[0133] Comparative Example 10:
[0134] Comparative Example 10 provides a hair repair composition using polyquaternium-52 as a raw material, which includes 8% fatty alcohol, 0.3% hydroxyethyl cellulose, 8% amino dimethicone, 4% polydimethicone, 1.5% polyquaternium-52, 0.3% keratin, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin, 0.05% kason and deionized water. The composition is prepared by the following steps:
[0135] S1. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.3% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0136] S2. After the emulsifying pot is heated to 85°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and keep the temperature at 83°C and stir until the mixture is evenly dissolved;
[0137] S3. Place 8% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifier pot, stir evenly and homogenize for 5 minutes, continue to keep at 83°C and stir at medium speed for 20 minutes before starting to cool down;
[0138] S4, after the temperature drops to 58°C, add 8% amino-terminated polydimethylsiloxane and 4% polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0139] S5. After the temperature drops to 43°C, add 1.5% polyquaternium-52, 0.3% keratin, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix evenly.
[0140] In Comparative Example 10, both polyquaternium-52 and aminodimethicone are added in large amounts. Due to the excessive amount of aminodimethicone, the overall experience is still sticky. Compared with the group without polyquaternium-52, the fluffiness is slightly improved.
[0141] Comparative Example 11
[0142] Comparative Example 11 provides a hair repair composition using polyquaternium-52 as a raw material, which includes 8% fatty alcohol, 0.3% hydroxyethyl cellulose, 0.5% amino dimethicone, 4% polydimethicone, 3% polyquaternium-52, 0.01% keratin, 1.8% stearyl trimethyl ammonium chloride, 0.6% behenyl trimethyl ammonium chloride, 0.1% chelating agent, 0.15% lactic acid, 0.3% DMDM hydantoin and 0.05% kason and deionized water. The composition is prepared by the following steps:
[0143] S1. First pour deionized water into the emulsifying pot, then add 0.1% chelating agent, stir at room temperature, then sprinkle 0.3% hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating to increase the temperature;
[0144] S2. After the emulsifying pot is heated to 85°C, add 1.8% stearyl trimethyl ammonium chloride and 0.6% behenyl trimethyl ammonium chloride in sequence, and keep the temperature at 83°C and stir until the mixture is evenly dissolved;
[0145] S3. Place 8% fatty alcohol (C16 / 18) in the oil phase pot and heat to 83°C until completely dissolved, then pour into the emulsifier pot, stir evenly and homogenize for 5 minutes, continue to keep at 83°C and stir at medium speed for 20 minutes before starting to cool down;
[0146] S4, after the temperature drops to 58°C, add 0.5% amino-terminated polydimethylsiloxane and 4% polydimethylsiloxane in sequence, and stir quickly to mix evenly;
[0147] S5. After the temperature drops to 43°C, add 1.5% polyquaternium-52, 0.01% keratin, 0.15% lactic acid and preservatives in sequence, and stir for about 20 minutes to mix well.
[0148] In Comparative Example 11, polyquaternium-52, a small amount of protein, and a small amount of aminodimethicone were added. Due to the spherical structure of polyquaternium-52, keratin, aminodimethicone, etc. were efficiently spread, thereby improving the smoothness of dry hair as a whole.
[0149] Fluffy performance test
[0150] Material preparation: Select the hair of the same woman, with a length of about 300 mm, cut off the hair ends and roots, and divide the hair into bundles of 15 g / bundle.
[0151] In order to reduce the interference of hair blowing, combing and living habits with the test results of fluffiness, the hair compositions of Examples 1-3 and Comparative Examples 1-11 were tested for hair fluffiness. The specific steps of the fluffiness test method include:
[0152] 1. Pre-cleaning: Wash the hair with 5% SLES solution once, and hang it in a constant temperature and humidity environment to dry overnight for later use;
[0153] 2. Pre-treat the hair bundle with 1% artificial sebum ethanol solution, dry it, then wash the hair bundle with the hair composition sample, and dry it naturally for later use;
[0154] 3. Wash the hair bundles with the hair composition to be tested, using 2 g for each hair bundle, rubbing for 30 seconds, and rinsing for 30 seconds;
[0155] 4. Hang the washed hair bundle in a constant temperature and humidity room (humidity 55%, temperature 22°C) to dry overnight;
[0156] 5. Observe and touch the fluffiness of the hair with your hands, and score it (using a 0-10 point scale, the higher the score, the better the fluffiness of the hair).
[0157] The test results are shown in Table 1
[0158] Fluffiness Example 1 8.5 Example 2 7 Example 3 8 Comparative Example 1 5 Comparative Example 2 6 Comparative Example 3 6 Comparative Example 4 7 Comparative Example 5 5 Comparative Example 6 5.5 Comparative Example 7 4 Comparative Example 8 6 Comparative Example 9 6 Comparative Example 10 5 Comparative Example 11 6.5
[0159] The fluffiness test of the compositions of Examples 1-3 and Comparative Examples 6, 7, 10 and 11 shows that the addition of polyquaternium-52 can neutralize the negative charge on the hair, making the hair light and fluffy; its unique spherical structure can improve the smooth and uniform spreading of amino-terminated polydimethylsiloxane and keratin hair conditioner on the hair, bringing a smooth and pleasant fluffy texture.
[0160] Conduct wet and dry combing force tests
[0161] Material preparation: Select the hair of the same woman, with a length of about 300 mm, cut off the hair ends and roots, and divide the hair into bundles of 15 g / bundle.
[0162] The test steps are as follows:
[0163] S1, measuring the dry combing force F1 of the hair bundle;
[0164] S2. Wash and massage the hair bundle with 2 mL of 10% sodium lauryl sulfate aqueous solution for 1 minute, rinse in tap water for 1 minute to avoid hair tangling; add 800 mL of deionized water to a 1000 mL beaker, immerse the hair bundle washed with the sodium lauryl sulfate aqueous solution in the water, take it out, remove excess water from the roots to the ends of the hair, and measure the wet combing force F2 of the hair bundle;
[0165] S3, treat a hair tress with 2 g of the hair repair composition prepared in Examples 1-3 and Comparative Examples 1-11, massage from the roots to the ends for 1 minute, rinse in tap water for 1 minute to prevent hair tangling, add 800 ml of deionized water to a 1000 ml beaker, immerse the hair tress treated with the hair repair composition in water, take it out, remove excess water from the roots to the ends, and measure the wet combing force F3 of the hair tress;
[0166] S4. After the hair is dried in a natural environment, the dry combing force F4 of the hair bundle is tested.
[0167] S5. Calculate based on the combing improvement effect: wet hair combing improvement = (F3-F1) / W0×100%; dry hair combing improvement = (F4-F2) / D0×100%.
[0168] The test results are shown in Table 2.
[0169] Improvement in wet hair combing power / % Improvement in dry hair combing ability / % Example 1 38 58 Example 2 29 52 Example 3 30 55 Comparative Example 1 28 48 Comparative Example 2 27 45 Comparative Example 3 25 43 Comparative Example 4 37 61 Comparative Example 5 16 26 Comparative Example 6 19 30 Comparative Example 7 18 28 Comparative Example 8 20 32 Comparative Example 9 32 38 Comparative Example 10 22 30 Comparative Example 11 27 50
[0170] It can be seen from the above experimental results that the hair repair composition containing a 3D structured cationic polymer provided in the present invention can greatly reduce the combing force, that is, it can greatly improve the smoothness of the hair bundle, that is, the formula has excellent conditioning effect on the hair.
[0171] Conduct mildness test
[0172] Materials preparation:
[0173] This test utilizes the characteristics of the intact, clear and transparent vascular system of the chorioallantoic membrane of mid-stage incubated chicken embryos. A certain amount of the test substance is directly exposed to the chorioallantoic membrane of the chicken embryo. After a period of action, the changes in the toxic effect indicators of the chorioallantoic membrane (such as bleeding, coagulation and vascular melting) are observed. These indicators reflect the changes in the morphological structure, color and permeability of the blood vessels and vascular networks, as well as the phenomena such as the denaturation of the chorioallantoic membrane proteins and the degree of damage. Finally, a score is obtained by combining them to evaluate the eye irritation of the test substance.
[0174] The test steps are as follows:
[0175] S1. Preparation of test substances
[0176] S1.1. Liquid test substances
[0177] The liquid test substance of the present invention is a hair repair composition and should be tested in the form of an undiluted original solution using the reaction time method;
[0178] Opaque liquid test substances (turbid and colored suspensions) should be tested using the endpoint evaluation method;
[0179] The opaque turbid liquid test substance can be dissolved / diluted with an appropriate solvent to become a transparent solution with the highest concentration and tested using the reaction time method. This experiment uses the endpoint evaluation method;
[0180] S1.2. Controls and preparation
[0181] Negative control: 0.9% sodium chloride solution is usually selected for flushing and negative control during the experiment.
[0182] Positive control: A known eye irritant should be set up for each test. If the purpose of the test is to identify corrosive or severely irritating substances, the positive control should be a substance that can produce a severe reaction, such as 1% SDS, 0.1 mol / L sodium hydroxide.
[0183] If the purpose is to evaluate the severity of the eye irritation of the test substance, positive substances whose reaction changes are not too drastic can be selected, such as acetic acid of different concentrations.
[0184] Solvent control: If the test substance is diluted with a certain solvent, the test should set up a solvent control.
[0185] Benchmark control: mainly used to prove the validity of the test method, especially to check the reactivity of each batch of chicken embryos, detect test substances with turbidity / special classification / special eye irritation, or evaluate the relative irritation ability of an eye irritant. The benchmark control substance should have the following characteristics: stable and reliable source, structure and function similar to the chemical classification of the test substance, known physical / chemical properties, known in vivo rabbit eye test effects, and known degree of expected reaction.
[0186] S2.CAM Preparation
[0187] Candling of 9-day-old chicken embryos, discarding unfertilized, inactive, defective, or thin-shelled embryos, first mark the location of the air chamber with a pen, open the shell with a mini cutter, and peel off the remaining shell in the air chamber along the opening position. Be careful not to damage the integrity of the egg membrane, use a pipette to moisten the egg membrane, and carefully use tweezers to remove the inner membrane to ensure that the vascular membrane is not damaged. At this time, the structure of the vascular system should be observed again. If it is intact, the next step of the test can be carried out.
[0188] S3. Detection
[0189] Take 0.3 mL of the squeezed test substance and apply it directly to the CAM, ensuring that at least 50% of the CAM surface is covered by the test substance. After 3 minutes of action, gently rinse the test substance on the CAM membrane with saline and observe the results within 30 seconds after the rinse is completed to observe the degree of change of each toxic effect.
[0190] If observations show that at least one reaction in all six embryos is scored as moderate or above, the test should be repeated.
[0191] S4. Results and observations
[0192] S4.1. Bleeding
[0193] Refers to the outflow of blood from the blood vessels and / or capillaries of the CAM. Bleeding can appear in various forms, such as cauliflower-like, smooth, diffuse gauze-like or punctate bleeding (due to the selective outflow of blood from different areas of the vascular membrane). Bleeding is graded and scored according to its severity.
[0194] a) No bleeding (0 points);
[0195] b) Mild bleeding (1 point): only bleeding from small blood vessels and a small amount of bleeding (such as 0.5% Texapon ASV, 5 minutes of action);
[0196] c) Moderate bleeding (2 points): bleeding from small and large blood vessels with significant blood outflow (e.g. 1.0% Texapon ASV, 5 min);
[0197] d) Severe bleeding (3 points): Almost all blood vessels bleed, with massive blood outflow (e.g. 5% Texapon ASV, 5 min). It should be noted that bleeding may be transient, and the massive bleeding observed in the first 30 seconds may cover the subsequent bleeding reaction.
[0198] S4.2. Coagulation
[0199] Refers to the denaturation of intravascular and extravascular proteins, which is usually only seen in large and medium-sized blood vessels and does not include changes in capillaries.
[0200] Thrombosis: It is intravascular coagulation, which is the interruption of blood flow in blood vessels caused by various reasons, such as changes in blood vessel pressure, swelling of blood vessel walls, etc., which manifests as dark coagulation spots in blood vessels.
[0201] Extravascular coagulation: It may appear as dark coagulation spots outside the blood vessels; it may also appear as turbidity (opacity), appearing in all or part of the membrane, and may be similar to milky white gauze, or milky. Careful inspection is required not to confuse coagulation with changes in the physical and chemical properties of the test substance in aqueous solution (such as the formation of colloids, precipitation, etc.). Coagulation should be graded and scored according to the severity.
[0202] a) No coagulation (0 points);
[0203] b) Mild coagulation (1 point): Mild coagulation inside and / or outside the blood vessels, and / or mild turbidity of the CAM membrane (mild coagulation such as 0.2% sodium hydroxide for 5 minutes, mild turbidity such as 0.3% acetic acid for 5 minutes);
[0204] c) Moderate coagulation (2 points): moderate intravascular and / or extravascular coagulation, and / or moderate turbidity of CAM membrane (moderate coagulation such as 0.3% sodium hydroxide for 5 minutes, moderate turbidity such as 3% acetic acid for 5 minutes);
[0205] d) Severe coagulation (3 points): severe intravascular and / or extravascular coagulation, and / or severe turbidity of CAM membrane (severe coagulation such as 0.5% sodium hydroxide for 5 minutes, severe turbidity such as 30% acetic acid for 5 minutes).
[0206] S4.3. Vascular dissolution
[0207] It refers to the disappearance of blood vessels on the CAM membrane, which may be caused by multiple factors such as bleeding and changes in vascular wall tension. Hemolysis is graded and scored according to the severity.
[0208] a) No vascular lysis (0 points);
[0209] b) Mild vascular thrombolysis (1 point): only small blood vessels are thrombosed (e.g. 0.5% Texapon ASV, 5 min);
[0210] c) Moderate vascular lysis (2 points): lysis of small and large blood vessels (e.g. 1% Texapon ASV, 5 min);
[0211] d) Severe vascular ablation (3 points): large vessels and the entire vascular tree are ablated (such as 5% Texapon ASV, 5 minutes).
[0212] S5. Endpoint Scoring (ES)
[0213] For tests conducted using the endpoint evaluation method, the endpoint score (ES) should be calculated and the result should be rounded to two decimal places: ES = the sum of the degrees of bleeding, coagulation, and vascular lysis observed in 6 chicken embryos. The eye irritation of the test substance should be classified according to the ES value.
[0214] Endpoint Scoring Irritation Category:
[0215] a) ES ≤ 12 no / mild irritation;
[0216] b) 12<ES<16 moderate irritation;
[0217] c) ES ≥ 16 Strong irritation / corrosiveness.
[0218] The eye irritation of the test substances was classified according to the ES values. The experimental results are shown in Table 3.
[0219] The test results are shown in Table 3.
[0220]
[0221]
[0222] It can be seen from Table 3 that under the experimental conditions of a hair repair composition containing a 3D structured cationic polymer of the present invention, according to the mildness test, the endpoint score obtained by the hair repair composition samples prepared by Examples 1-3 / Comparative Examples 1-3 / Comparative Examples 5-8 / Comparative Example 10 / Comparative Example 11 is about 10, indicating that the tested samples are non-irritating; while the endpoint score obtained by the samples of Comparative Example 4 / Comparative Example 9 is 20, indicating that the tested samples are moderately irritating.
[0223] Conduct stability testing
[0224] The test steps are as follows:
[0225] Samples of the hair repair compositions prepared in Examples 1-3 and Comparative Examples 1-11 were placed at 43° C., −15° C. and room temperature for 3 months, and the stability of the samples was observed to see if there were any delamination, water separation, taste change, or reddening.
[0226] The test results are shown in Table 4.
[0227]
[0228]
[0229] It can be seen from Table 4 that under the experimental conditions of the hair repair composition containing a 3D structured cationic polymer of the present invention, according to the stability test, excessive amino dimethicone and keratin cause the formula to easily turn red.
[0230] Comparison with Commercially Available Hair Masks The composition of Example 1 and a commercially available hair mask (Comparative Example 12) were respectively subjected to a combing force test and a crowd use comparison test (using a 0-10 point system, with a larger score indicating a better experience).
[0231] The test results are shown in Table 5.
[0232] Improvement in wet hair combing power / % Improvement in dry hair combing ability / % Example 1 38 58 Comparative Example 12 32 50
[0233] The test results are shown in Table 6
[0234]
[0235] It can be seen from Tables 5 and 6 that under the experimental conditions of the hair repair composition containing a 3D structured cationic polymer of the present invention, Example 1 has great advantages over commercially available hair masks in terms of dry and wet hair combing power and user experience.
[0236] The present invention discloses a hair repair composition containing a 3D structured cationic polymer and a preparation method thereof, and has the following beneficial effects: the 3D structured cationic polymer is a cationic spherical polymer, which can neutralize the negative charge on the hair and make the hair light and fluffy; its unique spherical structure enables keratin, amino-terminated polydimethylsiloxane, polydimethylsiloxane and other hair conditioners to be smoothly and evenly spread on the hair, bringing a smooth and pleasant texture; at the same time, it improves the combing properties of wet and dry hair, especially making the hair just after application, rinsing or drying very smooth, refreshing, non-sticky and having a good experience.
[0237] The present invention has been described in detail above. The above description is only a preferred embodiment of the present invention and should not limit the scope of implementation of the present invention. That is, all equivalent changes and modifications made within the scope of this application should still fall within the scope of the present invention.
Claims
1. A hair care composition containing a 3D structured cationic polymer, characterized in that: The components include the following weight fractions: Hair conditioning agent 5-14%, thickener 0.1-0.5%, emulsion stabilizer 7-9%, antistatic agent 1.4-3.0%, pH value adjuster 0.05-0.2%, preservative 0.2-0.4%, chelating agent 0.1% and deionized water 75-85%; The hair conditioning agent includes a 3D structured cationic polymer, keratin, amino dimethicone and polydimethicone.
2. A hair repair composition containing a 3D structured cationic polymer according to claim 1, characterized in that: The hair conditioning agent comprises 0.5-2.5% of a 3D structured cationic polymer, 0.02-1% of keratin, 3-8% of amino dimethicone and 0.5-4% of polydimethicone.
3. A hair repair composition containing a 3D structured cationic polymer according to claim 2, characterized in that: The keratin further comprises hydrolyzed keratin or oxidized keratin, and the 3D structured cationic polymer is polyquaternium-52.
4. A hair repair composition containing a 3D structured cationic polymer according to claim 2 or 3, characterized in that: The thickener is 0.1-0.5% hydroxyethyl cellulose.
5. A hair repair composition containing a 3D structured cationic polymer according to claim 4, characterized in that: The emulsion stabilizer is fatty alcohol (C16 / 18) 7-9%.
6. A hair repair composition containing a 3D structured cationic polymer according to claim 5, characterized in that: The antistatic agent is 1.2-2.0% of stearyl trimethyl ammonium chloride and 0.2-1.0% of behenyl trimethyl ammonium chloride.
7. A hair repair composition containing a 3D structured cationic polymer according to claim 6, characterized in that: The pH value adjuster is 0.15% lactic acid.
8. A hair repair composition containing a 3D structured cationic polymer according to claim 7, characterized in that: The preservatives are DMDM hydantoin 0.3% and kasone 0.05%.
9. A hair repair composition containing a 3D structured cationic polymer according to claim 8, characterized in that: The chelating agent is 0.1% disodium EDTA.
10. A method for preparing a hair care composition containing a 3D structured cationic polymer, characterized in that: The composition is prepared by the following steps: S1. First pour deionized water into the emulsifying pot, then add the chelating agent, stir at room temperature, then sprinkle the hydroxyethyl cellulose powder evenly into the water, continue stirring and turn on the heating; S2. After the emulsifying pot is heated to 80-85°C, add stearyl trimethyl ammonium chloride and behenyl trimethyl ammonium chloride in sequence, and stir at 80-85°C until dissolved evenly; S3. Place fatty alcohol (C16 / 18) in the oil phase pot and heat to 80-85°C until completely dissolved, then pour into the emulsifier pot, stir evenly and homogenize for 3-5 minutes, continue to keep at 80-85°C and stir at medium speed for 15-20 minutes before starting to cool down; S4. After the temperature drops to 55-60°C, add aminodimethylsiloxane and polydimethylsiloxane in sequence, and stir quickly to mix evenly; S5. After the temperature drops to 40-45°C, add polyquaternium-52, keratin, lactic acid and preservatives in sequence. Stir for about 20 minutes to mix well.
11. The method for preparing a hair repair composition containing a 3D structured cationic polymer according to claim 10, characterized in that: The weight fractions of each component are as follows: The deionized water is 75-85%, the chelating agent is 0.1%, the hydroxyethyl cellulose is 0.1-0.5%, the stearyl trimethyl ammonium chloride is 1.2-2.0%, the behenyl trimethyl ammonium chloride is 0.2-1.0%, the fatty alcohol (C16 / 18) is 7-9%, the amino-terminated polydimethylsiloxane is 3-8%, the polydimethylsiloxane is 0.5-4%, the polyquaternium-52 is 0.5-2.5%, the keratin is 0.02-1%, the preservative is 0.2-0.4%, and the pH regulator is 0.15%.